The difference of Reticulocyte Hemoglobin Equivalent Pre- and Post-Ultrafiltration Hemodialysis in Patients with Chronic Kidney Disease - Ni Made Rindra Hermawathi; Arifoel Hajat; Yetti Hernaningsih; Widodo Widodo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Chronic Kidney Disease (CKD) is a condition characterized by kidney damage and a decrease of Glomerular Filtration Rate of less than 60 mL/ min/1.73 m2 in more than three months. Anemia is the most common complication in patients with CKD who regularly undergo hemodialysis. Reticulocyte Hemoglobin Equivalent (Ret-He) is a new parameter that can reflect the storage of iron for erythropoiesis. This study compared the Ret-He level pre and post-hemodialysis and evaluated the effect of ultrafiltration (UF) hemodialysis to Ret-He level in CKD patients. This research was an observational analytical study. Samples were 50 patients with CKD who underwent hemodialysis regularly in Dr. Soetomo Hospital Surabaya by consecutive sampling from August–September 2017. The measurement of the Ret-He level pre ultrafiltration hemodialysis was divided into UF < 2 L and UF ≥ 2 L. Both groups showed homogenous results. The group with UF < 2 L increased significantly from pre to post ultrafiltration (p=0.010). The group with UF ≥ 2 L was not increased considerably from 30.57±3.62 to 32.69±3.45 (p=0.413). Ret-He level in the group with UF < 2 L was 0.81±1.10, significantly higher than the group with UF ≥ 2 L 0.12±0.83 (p=0.017). The difference of Ret-He level pre and post ultrafiltration was significant in UF < 2 L. There was a significant increase of the Ret-He level in hemodialysis with UF < 2 L compared to UF ≥ 2 L. The measurement of Ret-He should be performed before hemodialysis due to an increase in Ret-He after ultrafiltration hemodialysis.